2012
DOI: 10.1007/s12253-012-9558-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Fibrolamellar Hepatocellular Carcinoma

Abstract: Fibrolamellar hepatocellular carcinoma (FLC) occurs in non-cirrhotic liver and the etiopathogenesis is still obscure. Both hepatocellular and cholangiocellular markers are expressed in the tumor, however, molecular alterations and altered pathways playing role in the tumor pathogenesis are not clearly identified. The purpose of the present study was to compare the expression level of EGFR, syndecan-1 and ß-catenin in FLC, conventional hepatocellular carcinoma (cHCC) and cholangiocellular carcinoma (CCC) and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…CK7, HepPar-1) as well as neuroendocrine (e.g. PCSK1, NTS) lineages31112131415. We also have shown that FLCs are remarkably rich in cancer stem cells, unlike HCCs and CCAs, and that their gene expression profile more closely resembles that of primitive biliary tree stem cells than any other lineage stage of the liver16.…”
mentioning
confidence: 53%
“…CK7, HepPar-1) as well as neuroendocrine (e.g. PCSK1, NTS) lineages31112131415. We also have shown that FLCs are remarkably rich in cancer stem cells, unlike HCCs and CCAs, and that their gene expression profile more closely resembles that of primitive biliary tree stem cells than any other lineage stage of the liver16.…”
mentioning
confidence: 53%
“…Despite previous attempts to find frequently mutated cancer genes in FLC (i.e. KRAS and EGFR 11 ), none had been reported. By WES, FLC showed 23 damaging mutations, which included the well-known TSG BRCA2 implicated in DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant findings include molecular alterations of the MAPK/ERK 9 , ErbB 10 and Akt-mTOR 12 signaling pathways, few chromosomal aberrations based on comparative genomic hybridization data 13 , and no mutations in EGFR or KRAS genes 11 . More recently, a DNAJB1-PRKACA fusion protein caused by a deletion at chromosome 19 has been discovered in all 15 FLCs evaluated 14 .…”
Section: Introductionmentioning
confidence: 99%
“…FLC is a malignant hepatocellular tumor with distinct clinical and pathologic characteristics that differ from classical HCC, predominantly in FLC there is no consistent mutation, and shows fewer chromosomal abnormalities compared with HCC [2]. …”
Section: Discussionmentioning
confidence: 99%
“…It was first reported as a separate entity by Hugh Edmondson in 1956, who described the typical gross and microscopic features of this neoplasm as “a liver cell carcinoma in which stroma is profuse and the similarity of the cancer cells to normal cells is striking” [1]. Since then, it has been further studied, and its diagnostic criteria have been clearly established, the tumor express characteristics of conventional hepatocellular carcinoma (HCC) including cytokeratin 7 a cholangiocellular marker; however studies suggest that no consistent mutation is known in FLC so far [2]. …”
Section: Introductionmentioning
confidence: 99%